First Neotropical Mutualistic Associations in Bumblebee Nests (Hymenoptera: Apidae) - Gabriela Chavarria (Psyche: A Journal of Entomology)
Ectosymbionts of bumblebee nests of Bombus ephippiatus are recorded for first time from the American Tropics. An overview of this interaction is provided.